Hydrodynamics study and simulation of a bionic fish tail driving system based on linear hypocycloid. (5th April 2018) - Wang, Shuyan; Zhu, Jun; Wang, Xinguo; Li, Qinfeng; Zhu, Huiyun; Zhou, Rui
The tail driving system based on linear hypocycloid has the advantages of adjustable phase difference, no quick-return, and combining speed reducer with transformation mechanism. The two-joint composite motion of the driving system was realized via caudal peduncle's linear reciprocating in cosine and caudal fin's oscillating in sine-like. First, dynamic and hydrodynamic models were established with momentum theorem, Lagrange theorem, and two-dimensional Foil theory. Second, study on lift force and vortex ring with optimal results was further conducted by numerical simulation in FLUENT. At last, theoretical derivation and simulation results have been testified in experiments.